ACT OF COMMISSIVE PERFORMED BY M. JEFRI PRATAMA AS THE DEFENDANT IN THE JUDICIAL CASE OF JUDGE JAMALUDDIN’S MURDER - Fifi Safreni; Muhammad Ali Pawiro; Purwanto Siwi (Universitas Islam Sumatera Utara, 2023)
M. Jefri Pratama was the second defendant who participated in the planning and assisted in the execution of a heinous murder. It was proven that he had an affair and helped Zuraida Hanum kill her husband, as judge Jamaluddin wrote in the minutes of the court decision. This paper aims to explore the Searle’s in Yule (1996: 54) commissions, which were carried out by M. Jeffri Pratama, who was sentenced to death because of his involvement in the murder. The research method is descriptive-qualitative. In this context, M. Jefri Pratama uses commissive speech acts in his utterances, which mean he will take actions in the future. This includes the meaning of promising, threatening, refusing, pledging, offering, vowing, volunteering, and changes in statements, the actor’s speech situation, and the result. Its substance is seen in the discourse that leads to the meaning and order taken from the Medan High Court Decision. The purpose of this research is first to understand speech acts and the types of commissive speech acts, and second, to understand how the commissive speech acts influence people to carry out certain actions later in the murder case of Judge Jamaluddin. The results of this study have found four types of commissive speech acts: promising, offering, threatening, and refusing. Domination: the commissive speech acts produced by M. Jefri Pratama are threatening.